Catalyst‐Free Synthesis of 3‐Aryl‐3‐hydroxy‐2‐oxindole Derivatives by Using Water as the Solvent: Experimental and DFT Studies. Issue 11 (7th September 2016) - Kumar, Naveen; Kaur, Jasneet; Kumar, Akshay; Islam, Nasarul; Chimni, Swapandeep Singh
Abstract: A highly efficient catalyst‐free Friedel–Crafts reaction of isatin with phenol by using water as the solvent provided 3‐hydroxy‐2‐oxindole derivatives in excellent yields. DFT studies on various model systems suggested that the catalytic role of water involved activation of the reactant through hydrogen‐bonding interactions. Abstract : Cat on a hot isatin roof : A highly efficient catalyst‐free Friedel–Crafts reaction between isatin and phenol by using water as the solvent provided 3‐hydroxy‐2‐oxindole derivatives in excellent yields. DFT studies on various model systems suggested that the catalytic role of water involved activation of the reactant through hydrogen‐bonding interactions.